Environmental Contamination with Candida Species in Multiple Hospitals Including a Tertiary Care Hospital with a Candida auris Outbreak - Jessica Ann Kumar; Brandon Eilertson; Jennifer L. Cadnum; Chauna S. Whitlow; Annette L. Jencson; Nasia Safdar; Sarah L. Krein; Windy D. Tanner; JeanMarie Mayer; Matthew H. Samore; Curtis J. Donskey (Case Western Reserve University, 2019)
Background: Environmental sources have been implicated as a potential source for exogenous acquisition of Candida species, particularly the emerging multidrug-resistant Candida auris. However, limited information is available on environmental reservoirs of Candida species in healthcare facilities. Methods: During a 6-month period, cultures for Candida species were collected from high-touch surfaces in patient rooms and from portable equipment in 6 US acute care hospitals in 4 states. Additional cultures were collected from sink drains and floors in one of the hospitals and from high-touch surfaces, portable equipment, and sink drains in a hospital experiencing an outbreak due to C. auris. Candida species were identified using matrix-assisted laser desorption/ionization time-of-flight mass spectometry. Results: Candida species were recovered from patient rooms in 4 of the 6 hospitals. Seven of 147 patient room cultures (4.8%) and 1 of 57 (1.8%) portable equipment cultures were positive, with the most common species being C. parapsilosis. For the hospital where additional sites were sampled, Candida species were recovered from 8 of 22 (36.4%) hospital room floors and 4 of 17 (23.5%) sink drains. In the facility with a C. auris outbreak, Candida species were frequently recovered from sink drains (20.7%) and high-touch surfaces (15.4%), but recovery of C. auris was uncommon (3.8% of high-touch surfaces, 3.4% of sink drains, and 0% of portable equipment) and only present in rooms that currently or recently housed a patient with C. auris. Conclusion: Candida species often contaminate surfaces in hospitals and may be particularly common on floors and in sink drains. However, C. auris contamination was uncommon in a facility experiencing an outbreak, suggesting that current cleaning and disinfection practices can be effective in minimizing environmental contamination.